[tex] \huge\mathbb{ \underline{SOLUTION :}}[/tex]
Given:
[tex]\longrightarrow\bold{f(x)= \sqrt{7}}[/tex]
To solve for the inverse of a function we begin by re-writing the function as an equation in terms of y.
[tex]\bold{Becomes,}[/tex]
Next step we switch sides for x and y variables and then solve for the y variable as shown below,
[tex]\longrightarrow\sf{y= \sqrt{x}+7}[/tex]
[tex]\bold{Then,}[/tex]
[tex]\longrightarrow\sf{x= \sqrt{y}+7}[/tex]
[tex]\small\bold{Solve \: for \: y \: and \: subtract \: 7 \: from \: the \: both \: }[/tex] [tex]\bold{sides,}[/tex]
[tex]\longrightarrow\sf{x-7= \sqrt{y}}[/tex]
[tex]\small\bold{Square \: both \: sides }[/tex]
[tex]\sf{(x-7)^2=(\sqrt{y})^2}[/tex]
[tex]\sf{(x-7)^2=y}[/tex]
We now re-write in function notation. Take note however that this is the inverse:
[tex]\bold{Where \: y}[/tex] [tex]\sf{=(x-7)^2 }[/tex]
[tex]\longrightarrow\sf{y= (x-7)^2 }[/tex]
[tex]\huge\mathbb{ \underline{ANSWER:}}[/tex]
[tex]\large\boxed{\sf A. \: \: f^{-1}(x)= (x − 7)^2 , \: for \: \underline > 7 }[/tex]